(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objectives of the study are comparison of efficacy of Preperitoneal approach and Darning repair in patients with Inguinal Herni and also to compare the early recurrence in these procedures. Place and Duration of Study: Surgical Unit II, Sir Ganga Ram Hospital Lahore. Duration of study was 6 months i.e 1st january to June 2010. Materials and Methods: Patients from all age groups and both genders admitted through OPD (Male=45, Female=5). Prospective study using two procedures were adopted i.e Preperitoneal and Darning for the repair of Inguinal Hernias. Results: A total of 50 patients were studied out of which 45 were male and 5 female. All of these were operated, 20 were repaired using Darning and 30 by Pre-peritoneal approach. It was found that there was one day difference in the hospital stay of the patients in both procedures. Early recurrence was only associated with 2 procedures and only related to defective technique/ inexperienced Surgeon particulary incases of Preperitoneal Approach.